PPAR-γ Agonists for the Treatment of Major Depression: A Review - Colle, R.; de Larminat, D.; Rotenberg, S.; Hozer, F.; Hardy, P.; Verstuyft, C.; Fève, B.; Corruble, E. (Pharmacopsychiatry, 2017)
Introduction: Selective agonists of the nuclear transcription factor peroxisome proliferator-activated receptor-gamma (PPAR-γ) are used for the treatment of type 2 diabetes. We reviewed their efficacy and safety for the treatment of major depression and the association of their potential antidepressant effects with changes in biomarkers of metabolism and inflammation.Methods: From 8 studies, 4 open-label trials, and 4 randomized controlled trials (RCT) (3 vs. placebo and 1 vs. metformin), 448 patients with major depression were included, of which 209 patients received PPAR-γ agonists (pioglitazone or rosiglitazone) for 6–12 weeks, either alone or in add-on therapy to conventional treatments.Results: PPAR-γ agonists have antidepressant effects in the 4 open-label studies and in 3 out of 4 RCT. No major adverse event was reported. Improvement in depression scores was associated with improvement in 3 biomarkers of insulin resistance (homeostatic model assessment [HOMA-IR], oral glucose tolerance test, and fasting plasma glucose) and 1 biomarker of inflammation (interleukin-6) among 21 biomarkers studied.Conclusion: PPAR-γ agonists may have antidepressant properties, which need to be assessed in further studies of major depressive episodes.